Indonesia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This Selected Issues paper focuses on various challenges and opportunities related to reaping Indonesia's demographic dividend. Demographic trends can impact growth through various channels. These include the size of the labor force, productivity, and capital formation. Indonesia's growth is set to have a sizeable tailwind from demographic trends. The paper suggests that Indonesia should seize the window of opportunity to reap the demographic dividend, as aging is projected to start kicking in less than 15 years. In the long-term, Indonesia can grow old before becoming rich. The rapid speed of aging implies that Indonesia, similar to many Asian economies, may face the prospect of becoming old before becoming rich. Given Indonesia's favorable demographic trends, policies should focus first on maximizing the demographic dividend. Reaping the demographic dividend requires appropriate policies to raise productivity and create enough quality jobs for the growing working-age population. Investing in human capital early on, including education and health care, is essential to improve the productivity of the workforce and increase the size of the demographic dividend.